Photocatalytic Degradation Of Tetracycline In Aqueous Solution By Zno Quantum Dots/Tio2 Supported Catalysts - Saidu, Usman (2021)
In this research, TiO2 nanoparticles (TiO2 NPs) were incorporated with 3%, 5%, 8%, and 10% ZnO quantum dots (ZnO QDs) via sol-gel method. The photocatalyts (xZnO QDs/TiO2; x= 3%, 5% 8% and 10%) were characterized using Xray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), atomic force microscopy (AFM), high resolution transmission electron microscopy (HRTEM), field emission scanning electron microscopy (FESEM), ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS) Brunauer-Emmett-Teller (BET), X-ray photoelectron spectroscopy (XPS), and photoluminescence (PL) analyses. The synthesized photocatalysts' efficiency in suspended form was tested in the photodegradation of tetracycline (TC) under visible light irradiation. About 95% degradation of TC was achieved within 90 min of visible light illumination using 8%- ZnO QDs/TiO2, under the optimized conditions: TC concentration = 40 mg/L, pH = 9, catalyst dosage = 250 mg/L. The 8%-ZnO QDs/TiO2 nanocomposite photocatalyst was immobilized on linear low-density polyethylene (LLDPE) polymer using the solution casting method. The LLDPE supported composite films (ZnO QDs/TiO2@LLDPE), each with a different amount of 8%-ZnO QDs/TiO2 nanocomposite (2, 5, 8, and 10 wt.%) were characterized by FTIR, XRD, FESEM, UV-vis-DRS, AFM, water contact angle, differential scanning calorimetry (DSC), and thermogravimetric (TGA) analyses. Structural and morphological studies revealed that the nanocomposites were homogenously dispersed and embedded onto the LLDPE matrix.